#banggabuatanindonesia Social Marketing of #banggabuatanindonesia as Indonesian National Identity Campaign in Social Media - Rotumiar Pasaribu (ULTIMA Comm, 2023)
#banggabuatanindonesia is one of social marketing campaign activity which focus on building selling andbuying habit for the Indonesian people. This activity is created to raise the Indonesian economic sector bycampaigning the domestic product. The worries also came while the Indonesian people are prouder to usethe product from foreign country. This problem brings the bad effect weather for the economic cycle ofdomestic product selling. Furthermore, this case also wants to solve the nation identity crisis from economicsector by campaigning #banggabuatanindonesia. The purpose of this campaign is to educate the seller whosell the product and the customer to be proud of domestic product. Beside make the cycle of nationeconomic more stable, this activity also aims to create Indonesia Nation Identity campaign by domesticproduct. This campaign uses social media to spread the information. From that information, this researchwants to focus on the measurement of the campaign which use social marketing tool in social media withhashtag #banggabuatanindonesia. The measurement of the campaign uses input, output, outtake andoutcome tools. The social marketing activities focus on marketing mix which consist of product, price,place and promotion. This research uses qualitative approach which focus on content analysis method. Theresult show that there are so many new account members which use #banggabuatanindonesia socialmarketing as promotion strategy and help campaigning Indonesia identity. That activity gives the lessonfor the seller to create good domestic product and marketing activity. in other side, the consumer gets thelesson and can buy domestic product. As a result of understanding Indonesia nation identity, between theseller and consumer create #banggabuatanindonesia campaigning activity from transactional activity insocial media. Finally, this activity gives good impact such as the development of selling domestic product,having Indonesia economic positive circulation and also establishing Indonesian nation identity campaign.